Symposium 1: Relationality, Networked Learning and Árbediehtu- traditional Sámi knowledge - Parfa Koskinen, Katarina (Proceedings of the International Conference on Networked Learning, 2024)
The purpose with this paper is firstly to investigate whether an Indigenous, multidimensional, relationally intertwined onto-epistemology is present in a policy document regarding árbediehtu, traditional Sámi knowledge. The policy identify knowledge claims the Sámi parliament in Sweden wants to pass on to future generations, and is the closest to a Sámi produced curriculum we get in a Swedish context. A four-dimensional relational framework where relationality is unpacked through resonance theory by Hartmut Rosa is utilised as an analytical tool. Secondly, implications for Networked Learning, especially as occurring in remote Sámi language education, are elaborated on. The findings show that the framework can be helpful for understanding and describing a multidimensional relational onto-epistemology as relationships in the policy can be identified on three of the four dimensions in the framework. The last dimension involves the self and is mainly a reflexive tool. However, as the discussion initiated in the concluding section indicates, implications for Networked Learning and remote Sámi language education is not the only take-away. An unpacked understanding of relationality offers a glocalised as-well-as theoretical approach, which is important both locally and globally as issues of sustainability call for the development of a new social contract. According to resonance theory, resonant relationships are transformational, leading to the conclusion that a relational approach can lead to an increased understanding of learning and knowing, and a sense of self-efficacy and a stronger identity, all important aspects in transformational education. Further, the study is an example of how a national graduate school, GRADE, can offer epistemic space when researching digital technologies in education.